The challenges of EU governance and the quest for long-term growth - Renaud Thillaye (WWWforEurope, 2013)
The research paper assesses the opportunities and challenges raised by the post-crisis EU governance system with regard to the transition of European economies towards a new growth model balancing economic performance with social cohesion and environmental responsibility. It begins with questioning the term of `governance' and with a hint at the 'multi-level governance' literature available in EU studies. This section suggests that the EU's nature is one of multiple and innovative policymaking methods. Any assessment of the EU's added value must investigate the actual policy direction and the effectiveness of a complex EU governance architecture, by looking in particular at how EMU coordination frameworks interacts with Community-based policies. The paper focuses then on the goals, the processes and the financial instruments underpinning the Europe 2020 Strategy, bearing in mind the limits encountered by the Lisbon Strategy during the last decade. It finds that the Strategy, albeit carefully balanced, does not avoid the risk of a 'capability-expectations' gap. Implementation would gain, on the one side, from more consistent legal and financial instruments at EU level, and from a more supportive macroeconomic environment in the euro area on the other. The third section examines the way in which Europe 2020 cohabits with other frameworks of coordination within the European Semester, such as the reformed Stability and Growth Pact, and the new Macroeconomic Imbalance Procedure. Potential clashes between diverging objectives and their legal bases are identified and tested against the views of practitioners (8 interviews were conducted in parallel to the research) and throughout a case-study based on how the Semester has so far impacted on three countries: Finland, France and Italy. The European Commission's Annual Growth Surveys for 2011, 2012 and 2013 are also analysed. This research reveals a prioritisation of fiscal consolidation and short-term, market-based adjustment policies over the longer-term objectives pursued by the Europe 2020 Strategy. The collective outcome of these policies, and the impact of national reforms on the whole EU, tend to be overlooked as well. Nevertheless, there is substantial room for manoeuvre and dialogue between the Commission and individual countries. The paper concludes that ways should be found to shield Europe 2020 objectives from overwhelming stability considerations in the Euro Area, and contains some suggestions for further innovations of governance in that respect. A greater differentiation between countries according to their position might be necessary. The conclusion also argues that it fells to national governments, parliaments and parties to seize the opportunity of the European Semester to frame challenges differently and to push for alternative solutions.
Keywords: E02; 330; Economic strategy; EU integration; European economic policy; European governance; European Monetary Union; Good governance; Institutional reforms